EVALUASI PROGRAMP'ENOIOIKAN INKLUSIF 01 SO NEGERI GEJAYAN KABUPATEN SLEMAN YOGYAKARTA - J. Wantah, Maria (Cakrawala Pendidikan, 2008)
This study aims to describe (1) the relevance of the implementation of theinclusiveprogram for children with special needs; (2) input characteristics of thoseinvolvedin the inclusive program; (3) the learning process; and (4) benefits of theinclusiveprogram for children with special needs and the sustainability of theprogram. Thedata sources were classroom teachers, special guide teachers, and theprincipal. Thedata were collected through observations, interviews, andquestionnaires using the CIPP (Context Input Process Product) model. The datawere analyzed using the. descriptive qualitative methodon the basis of certaincriteria. The research findings show that the implementation of the inclusiveprogram in SDN .Gejayan is carried out in order to provide children with specialneedswith education together with normal children in regular classes. The resultsofthe input evaluation show that there are 23 children with special needsconsisting of 1 blindchild,.l child with severely low vision, 1 mentally disabledchild,,1 autistic child, and 19 children with learning difficulties. There are 2 specialguide teachers for deaf children and autistic' children with learning difficulties, sothat the implementation of education for childrenwith special needs has not metthe criteria.Â· Learning activities for childrenwith special needs are carried out twicea weekby special guide teachers. The results of the product evaluation show thatchildrenwith special needs can benefit from the implementation of the inclusiveprogram because they are allowed to learn together with normal childreninregular classes although their achievement is not as good as that of normalchildren.